INTERAKSI VARIETAS PEPAYA DAN PENYIRAMAN TERHADAP KUTU PUTIH Paracoccus marginatus Williams & Granara de Willink, (HEMIPTERA:PSEUDOCOCCIDAE) - Tairas, Robert W.; Pelealu, J.; Tulung, M. (EUGENIA, 2016)
abstract This study aims to understand the interaction of varieties and watering the papaya mealybug in Bangkok and local plants. Research using Completaly Randomized design (CRD) with treatments that Papaya of varieties Bangkok, Lokal, and Watering. Parameters measured were population nymph, imago, and the attack rate of the mealybug P. marginatus on the part of the plant consists of a trunk, the upper leaves, leaves the middle, and bottom leaves. The results showed that the population of nymphs on papaya local watering every day at the upper leaves of the plant has the highest population as much as 71.85 individuals per leaf and the lowest found in papaya Bangkok on watering every three days on the underside of leaves of plants of 1.85 individuals per leaf. Imago population at the local papaya with a watering every day at the middle leaf has the highest population of 27.85 individuals per leaf and the lowest found in papaya Bangkok with a watering every three days at the bottom of the leaf has a population of 1.71 individuals per leaf. The percentage of mealybug attacks were highest in local varieties of papaya with every day watering time (90.89%), followed by papaya local time watering every two days (70.35%), papaya Bangkok time watering every day (67.92%), local papaya time watering every three days (57.32%), papaya Bangkok time watering every two days (42.72%), and papaya Bangkok time watering every 3 days (40.04%). Keywords: Paracoccus marginatus, mealybug, papaya, population, watering